Naso frontal lesions in the midline of children - Lugo Machado, Juan Antonio (2015)
Objective: To determine the prevalence of midline nasofrontal lesions in a tertiary hospital of regional referral and it´s relationship with other malformations. Material and Methods: Study Design: Transversal retrospective. Male and female patients aged 1 month to 13 years of age with congenital lesions of the nasofrontal midline, treated at Children's Hospital from 1990 to 2005. Sample: was obtained by a non-probabilistic sample of consecutive cases. Through the Statistical Package for the Social Sciences (SPSS) version 13.0 which included descriptive statistics: median as a measure of central tendency and frequency distribution and proportion as a measure of dispersion. Results: a review of clinical records was conducted from 1990 to 2005, finding 38 of 67 records reviewed, 29 files were excluded because they correspond to the diagnosis of occipital encephalocele. Prevalence was 38 cases in 15 years. The gender distribution of nasofrontal midline lesions was slightly higher in females with 22 cases and 16 cases in males. The midline nasofrontal lesions found were midline encephalocele, gliomas and dermoid cysts. In our review most encephaloceles were not associated with the central nervous system and 11 cases did have an associated disorder; 5 cases with hydrocephalus and / or temporal or occipital cysts and 6 cases with nondevelopment of the corpus callosum plus hydrocephalus. Conclusion: Our prevalence was 38 cases in 15 years. Nasofrontal midline lesion disgnosis are usually made in the first months of life. Among the types of midline nasofrontal lesions, the most common type found in our series was encephaloceles, followed by dermoid cysts. In the encephaloceles type of lesion, the most common one was frontoethmoidal, similar to reports in the literature. The most common malformations associated in this series were brainstem agenesis, hydrocephalus and temporal / occipitalcysts.